Impact of Macroeconomic News on Malaysian Bond Credit Spreads - SAID , Rasidah Mohd (Asian Journal of Empirical Research, 2013)
This study investigates the impact of scheduled macroeconomics news on credit spreads of Malaysian bonds of various maturities and rating groups. Using daily spreads from August 2006 through October 2009, the impact of macroeconomic news announcements on the Malaysian bond credit spreads is evident in this study. The results of the analyses show that prior to the release of the macroeconomic information, the persistency of volatility is lower when compared to the persistency for the whole sample period of study. This low persistency remains even after the announcement has been made especially for the high-grade investment bonds. The announcements, however, cause substantial reactions in the moderate and lower rating bonds. This implies that the higher the risk premium the bond carries, the more it will be affected by the announcement of macroeconomic news.